Self-Growth of Centimeter-Scale Single Crystals by Normal Sintering Process in Modified Potassium Sodium Niobate Ceramics - Ahn, Cheol-Woo (2016)
In this manuscript, an interesting phenomenon is reported. That is the self-growth of single crystals in Pb-free piezoelectric ceramics. These crystals are several centimeters in size. They are grown without any seed addition through a normal sintering process in modified potassium sodium niobate ceramics. It has been achieved by the composition designed to compensate the Na+ loss which occurs during the liquid phase sintering. The composition of the crystals is (K0.4925Na0.4925−xBa0.015+x/2)Nb0.995+xO3 [x is determined by the Na+ loss, due to Na2O volatilization]. These crystals have high piezoelectric voltage coefficients (g33, 131 10−3Vm/N), indicating that they are good candidates for piezoelectric sensors and energy harvesting devices. We hope that this report can offer the opportunity for many researchers to have an interest in these crystals.